The angel makers : arsenic, a midwife, and modern history's most astonishing murder ring - McCracken, Patricia Nell (New York : William Morrow, an imprint of HarperCollinsPublishers, 2023)
"The horror occurred in a rustic farming enclave in modern-day Hungary. To look at the unlikely lineup of murderesses--village wives, mothers, and daughters--was to come to the shocking realization that this could have happened anywhere, and to anyone. At the center of it all was a sharp-minded village midwife, a "smiling Buddha" known as Auntie Suzy, who distilled arsenic from flypaper and distributed it to the women of Nagyrév. "Why are you bothering with him?" Auntie Suzy would ask, as she produced an arsenic-filled vial from her apron pocket. In the beginning, a great many used the deadly solution to finally be free of cruel and abusive spouses. But as the number of dead bodies grew without consequence, the killers grew bolder. With each vial of poison emptied, a new reason surfaced to drain yet another. Some women disposed of sickly relatives. Some used arsenic as "inheritance powder" to secure land and houses. For more than fifteen years, the unlikely murderers aided death unfettered and tended to it as if it were simply another chore--spooning doses of arsenic into soup and wine, stirring it into coffee and brandy. By the time their crimes were discovered, hundreds were feared dead." -- Book jacket.
Includes bibliographical references (page 313)
Keywords: Women murderers -- History -- 20th century; Women serial murderers -- History -- 20th century; Serial murders -- History -- 20th century; Serial murderers -- History -- 20th century; Murder -- History -- 20th century; Murderers -- History -- 20th century; Murder -- Hungary; Arsenic -- Toxicology; Poisoning; Hungary -- History -- 20th century; True crime stories; Case studies